Pergbseran Peran Sosial Tuan Guru dalam Masyarakat Jambi Seberang (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This article highlights the positions and functions of Tuan Guru (Islamic prominent leaders) in Jambi Seberang in the past, in recent day and the decline of their social functions and roles. Once, they were very influential toward the shaping of Islamic culture amidst the society. Their roles and functions underwent changing due to the social dffirentiation and the specialization offunctions, as well. These declines are also due to the rapidflow of science and technology. They must adapt to these changes by accommodating the recent need of transformation and innovation of the educational systems of their pesantrens and madrasah (both are Islamic schools) in order to keep abreast with the societal-industrial needs and demands.